Are physiotherapists employing person-centred care for people with dementia? An exploratory qualitative study examining the experiences of people with dementia and their carers - Abigail J. Hall (BMC Geriatrics, 2018)
Abstract Background People with dementia may receive physiotherapy for a variety of reasons. This may be for musculoskeletal conditions or as a result of falls, fractures or mobility difficulties. While previous studies have sought to determine the effectiveness of physiotherapy interventions for people with dementia, little research has focused on the experiences of people receiving such treatment. The aim of this study was to gain an in-depth understanding of people’s experiences of receiving physiotherapy and to explore these experiences in the context of principles of person-centred care. Methods Semi-structured interviews were undertaken with people with dementia or their carers between September 2016 and January 2017. A purposive sampling strategy recruited participants with dementia from the South West of England who had recently received physiotherapy. We also recruited carers to explore their involvement in the intervention. Thematic analysis was used to analyse the data. Results A total of eleven participants were recruited to the study. Six people with dementia were interviewed and five interviews undertaken separately with carers of people with dementia. Three themes were identified. The first explores the factors that enable exercises to be undertaken successfully, the second deals with perceived resource pressures, and the final theme “the physiotherapy just vanished” explores the feeling of abandonment felt when goals and expectations of physiotherapy were not discussed. When mapped against the principles of person-centred care, our participants did not describe physiotherapy adopting such an approach. Conclusion Lack of a person-centred care approach was evident by ineffective communication, thus failing to develop a shared understanding of the role and aims of physiotherapy. The incorporation of person-centred care may help reduce the frustration and feelings of dissatisfaction that some of our participants reported.